(3JGL GddZI hUMGM GdYQHjIs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi fhGdg CeG HYO , aEfi bO ChOYJ gPG GdcJGH eG UM YfOi ef gP GddZI GdJi TQa Gddg efRdJgG , hLYd gde GdOjf hGdOfjG efhWkG HeYQaJgG s
(3BNQgG (B:s
(3HGdefGOi ai bhdg (B" (3jhSa CYQV Yf gPG (B" (3EP cGf GdeQGO eYdhekG bGd Ph GdQeI (B:- (3CdG jG GSdei jG OGQei Ydi GdHdi hdG RGd efgdkG HLQYGFc GdbWQ gPG BNQ cJGH GdUMGM , hGdMeO ddg s
(3ai GdeYgO fSNJGf HYfhGf (B: (3JGL GddZI hUMGM GdYQHjIs
(3GfXQgeG ai GdLRA GdChd HQbe (B29 (3, (B30 (3dZI s
(3fSNI KGdKI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs